High-coverage targeted lipidomics revealed a novel serum lipid dysregulation profile in adult growth hormone deficiency - Hongbo Yang; Meiping Chen; Lingjuan Jiang; Linjie Wang; Lian Duan; Fengying Gong; Huijuan Zhu; Hui Pan (Endocrine Connections)
Purpose: Patients with adult growth hormone deficiency (AGHD) are at an increased risk of metabolic syndrome. Despite extensive research efforts in recent decades, the lipid metabolism pattern of AGHD has yet to be thoroughly characterized. Methods: In this study, we used lipidomics analysis of fasting serum samples from 30 AGHD patients with intracranial germ cell tumors (iGCTs) and 30 age-, gender- and body mass index (BMI)-matched healthy controls to investigate the serum lipidomic pattern of AGHD patients with iGCTs. We meticulously quantified 534 serum lipids from 29 classes using high-coverage targeted lipidomics technology in conjunction with a robust bioinformatics pipeline. Results: Our results revealed an AGHD-specific dynamic change in the serum lipidomic profile, manifested by higher overall levels of many lipid subclasses, including triacylglycerols (TAGs), diacylglycerols (DAGs), phosphatidylglycerols, phosphatidylethanolamines (PE), phosphatidylcholines (PC), phosphatidylinositols, ceramides and bis(monoacylglycerol)phosphates, than in healthy controls and a distinct lower level for alkyl PE (PE-O) and alkyl PC (PC-O). AGHD individuals with nonalcoholic fatty liver disease showed specific changes in higher TAG and DAG subclass levels. Alterations in lipid profiles may contribute to metabolic dysregulation in AGHD patients. TAGs, PCs and PE fatty acids positively correlated with BMI, fasting insulin, insulin resistance index and adverse lipid parameters. In contrast, ether-linked PE-O, PC-O and LysoPE-O showed a negative correlation. Conclusions: This study has significantly expanded the current understanding of lipid dysregulation in AGHD patients with iGCT. These findings can potentially guide future research and development of monitoring and intervention strategies.